Giant osteoma of the ethmoidal sinus - Marambaia, Otavio; Gomes, Amaury de Machado; Marambaia, Pablo Pinillos; Pinheiro, Maili; Almeida, Fabio Siqueira Costa (International Archives of Otorhinolaryngology, 2009)
Introduction: The osteomas are osseous lesions with slow and asymptomatic growth that most of the times is a finding in radiological exams requested for other reason. It's the most common benign neoplasm of the paranasal sinuses. The osteomas are located mainly in the frontal sinus (57% to 80%), followed by the ethmoidal sinuses (20%), maxillary sinuses and rarely in the sphenoid sinus. It has a discreet predominance in the male sex 1.5 and its incidence is higher in the 3rd and 4th decades of life. The treatment is surgical no matter the size. Objective: To describe a case of giant osteoma of the ethmoidal sinus including a brief literature review. Case Report: JDA, male, 33 years old, presented with a right constant nasal obstruction for 01 year. Upon exam, he presented with facial asymmetry with lateralization of the right ocular globe. The computed tomography of the paranasal sinuses showed a lesion with density of soft parts occupying partially the right nasal cavity, ethmoid sinus and right maxillary. The patient was submitted to surgery with full exeresis of the lesion. The anatomopathological exam confirmed osteoma. The patient evolved without evidences of the lesion recurrence. Final Comments: The osteomas in the ethmoidal sinus, irrespectively of the size and due to the risk of complications, must be operated.